ANALISIS KINERJA SUPPLY CHAIN MANAGEMENT BERBASIS BALANCED SCORECARD PADA PT. ALOVE BALI IND - Tanaka, Dannis; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 7 No 7 (2018)DO - 10.24843/EJMUNUD.2018.v07.i07.p10, 2018)
The purpose of this study is to determine whether the performance of a company's supply chain management has been done well viewed from. This research was conducted at PT. Alove Bali IND. The number of samples taken as many as 20 employees of PT. Alove Bali IND and 5 agents PT. Alove Bali IND, Data collection is done through questionnaires and interviews. Data analysis techniques used to use. Based on the results of the analysis that has been found, PT.Alove Bali IND Regarding Changes malalui financial perspective is not good due to fluctuating in the year 2012 until 2014 and in running its operations the company is still very dependent by debt. On the perspective of the company's performance of the company has been fairly good physical average of all respondents is 4.20. On the internal business perspective the company's performance has been very good. On the perspective of learning and performance growth of the company has been very good because the average of all respondents is 4.61. Keywords: supply c hain m anagement, balanced s corecard , operation management